Protein recovery from yellow peas (Pisum sativum L.) for enhanced processing sustainability and functional properties - Guraya, Maria Angeles (2024)
This research focuses on sustainable protein recovery methods from a new yellow pea variety by examining alternative pH-shifting processes. The study focuses on reducing water consumption during alkaline extraction by adjusting solid-liquid ratios, and evaluating the impact of various isoelectric precipitants, including lactic acid and lactic acid bacteria (Lactobacillus plantarum and Lactobacillus lactis), on the functional and antioxidant properties of products across a wide range of pH values. It was here found that the process alternative with three 1:10 (w/v) extraction cycles and lactic acid bacteria as precipitant agent achieved high process productivity (0.36 kg protein product/kg pea flour) and low specific water consumption (94.9 kg water/kg protein product). No significant differences were observed in protein content and yield when compared to other flour-water ratios with higher water consumption or less eco-friendly precipitants. Products precipitated with lactic acid bacteria formed stable emulsions even at the isoelectric point, exhibited superior free radical scavenging activity, although solubility and water holding capacity were lower, and no differences were noted in oil holding capacity, foaming capacity, and foam stability.